INFLUENCE OF PROCUREMENT EXPERTISE ON PROCUREMENT REGULATORY COMPLIANCE LEVEL IN PUBLIC UNIVERSITIES IN KENYA - Ndung'u, Nderui; Were, Dr. Susan; Mwangangi, Dr. Patrick (International Journal of Supply Chain Management, 2020)
Purpose: This research focused on the influence of procurement expertise on procurement regulatory compliance level in public universities in Kenya. Methodology: This study adopted the ex-post facto survey research design. The target population was a total of thirty one chartered public universities in Kenya, which acted as the unit of analysis. The study sample comprised of 333 respondents with respect to the unit of observation which included, chief procurement officers, Principal procurement officers, senior procurement officers and procurement officers. This study adopted a census because the sample size of the study was small. This study further used questionnaires to collect primary data similar to the previous research projects. Questionnaires contained closed and open-ended questions. The pilot study was conducted at Jomo Kenyatta University of Agriculture and Technology. Data collected from the field was coded and cleaned to remove outliers or missing values and categorized manually according to the questionnaire items using frequency distribution tables and percentages. The researcher used both descriptive and inferential statistics with the help of statistical package of Social Science (SPSS) version 24 to analyze the data. Results and Findings: Regression of coefficients results revealed that procurement expertise and procurement regulatory compliance level are positively and significantly related (Î² =0.667, p=0.000). The findings indicated that there have been a low number of training sessions conducted on procurement. The deficient professionals in the department may have contributed to the low compliance level to the regulation of procurement and performance of procurement in the public universities. The findings revealed that most of the staff are not certified to be procurement expertise through certification and registration with higher professional bodies who oversee the skills of the members and therefore ensure the members are well equipped with procurement knowledge. Unique contribution to theory, policy and practice: It's essential to raise the level of professionalism in the procurement practices. The education of the employees guarantees that the procurement officers can read and understand the set guidelines in procurement in order to comply with the guidelines as set. Occurrences of missed deadlines in the procurement department should be minimized. Certification and registration with higher professional bodies who oversee the skills of the members ensure the members are well equipped with procurement knowledge. Procurement expertise was found to have a significant effect on the procurement regulatory compliance level.